2021
DOI: 10.3390/foods10081830
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Ultraviolet-Visible Spectroscopy for the Differentiation of Spanish Vinegars According to the Geographical Origin and the Prediction of Their Functional Properties

Abstract: High-quality wine vinegars with unique organoleptic characteristics are produced in southern Spain under three Protected Designations of Origin (PDO), namely “Jerez”, “Condado de Huelva” and “Montilla-Moriles”. To guarantee their authenticity and avoid frauds, robust and low-cost analytical methodologies are needed for the quality control and traceability of vinegars. In this study, we propose the use of ultraviolet-visible spectroscopy in combination with multivariate statistical tools to discriminate Spanish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Nevertheless, going to specific scenarios of food quality assessment, many works can be found in the literature as example of successful applications of UV-vis technology in the authentication of wine, vinegars, and other foodstuff [15,18,41,42]. In addition, the capability of UV-vis for the authentication of vinegars has been also supported by a recently research paper of other authors [19]. The software approach, even being a first prototype, is simple but reliable.…”
Section: Future Software Applicationmentioning
confidence: 95%
See 2 more Smart Citations
“…Nevertheless, going to specific scenarios of food quality assessment, many works can be found in the literature as example of successful applications of UV-vis technology in the authentication of wine, vinegars, and other foodstuff [15,18,41,42]. In addition, the capability of UV-vis for the authentication of vinegars has been also supported by a recently research paper of other authors [19]. The software approach, even being a first prototype, is simple but reliable.…”
Section: Future Software Applicationmentioning
confidence: 95%
“…Nevertheless, among the aforementioned strategies that have enabled the characterization and classification of them according to their origin or category, UV-vis spectroscopy has demonstrated in the last few years its great ability to characterize and classify wine vinegar according to their quality, particularly those with a protected designation of origin (PDO), and to their production process or aging time, showing successful results and opening up the possibility of developing an efficient quality control tool [15][16][17][18][19]. UV-vis spectrum of wine vinegars, and also wines, presents absorption bands in the range 300-400 nm related to absorbent species relevant for color and taste characteristics, such as polyphenolic compounds (e.g., some acids as hydroxycinnamic acids, some aldehydes such as benzaldehyde, stilbenes, flavanols, and anthocyanins), together with the presence of other compounds such those related to the grape-must caramel added to the vinegars [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although high-resolution mass spectrometry is the gold standard for non-targeted metabolomics, the implementation of large-scale targeted platforms has emerged in recent years for comprehensive and quantitative metabolomics fingerprinting [ 23 ]. Alternatively, spectroscopic techniques, such as near-infrared spectroscopy (NIR), mid-infrared spectroscopy (MIRS), RAMAN spectroscopy, ultraviolet-visible (UV-Vis) spectroscopy, and nuclear magnetic resonance (NMR), have also demonstrated great potential for food fingerprinting due to their capacity to simultaneously detect many compounds in a fast, non-destructive, and cost-moderate manner [ 24 , 25 , 26 ].…”
Section: Analytical Approaches In Food Authenticity Researchmentioning
confidence: 99%
“…Many of the original research articles published in this Special Issue revolve around the implementation of low-cost, ecofriendly, and non-destructive spectroscopic methods as a reliable alternative to traditional chemical-based analytical approaches for simple and rapid food authentication. In this respect, González-Domínguez et al described the potential of ultraviolet-visible spectroscopy in combination with multivariate statistical tools to discriminate Spanish wine vinegars produced under three Protected Designations of Origin (PDO), namely, "Jerez", "Condado de Huelva", and "Montilla-Moriles" [4]. Additionally, regression analysis demonstrated that spectral data could accurately predict the physicochemical and functional properties of vinegars, particularly their total phenolic content and antioxidant activity.…”
mentioning
confidence: 99%